2010
DOI: 10.1017/s0025315410001888
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in mortality and effects of by-catch on common bottlenose dolphins,Tursiops truncatus, in southern Brazil

Abstract: The mortality of the bottlenose dolphin, Tursiops truncatus, on the southern portion of Rio Grande do Sul State coast was investigated based on 914 beach surveys conducted between 1969 and 2006. A total of 188 stranded bottlenose dolphins were recorded during this period, indicating a 1.8M:1F sex-ratio of those animals sexed (N = 79). Mortality was low in calves, high in juveniles and sub-adults and slightly lower than in adults. The overall mortality was clearly seasonal overlapping with higher fishing effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 31 publications
1
67
0
7
Order By: Relevance
“…In contrast, in the southeastern region, stranded animals were mostly older dolphins, irrespective of sex. (Fruet et al, 2012). These results should, however, be taken as preliminary, particularly because the dataset from both regions contains a mix of individuals that died of natural and fisheries-related causes; the sample size in the southeastern area is small and therefore stochasticity may account for much of this pattern.…”
Section: Age Structure Of Stranded and Incidentally-caught Dolphinsmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, in the southeastern region, stranded animals were mostly older dolphins, irrespective of sex. (Fruet et al, 2012). These results should, however, be taken as preliminary, particularly because the dataset from both regions contains a mix of individuals that died of natural and fisheries-related causes; the sample size in the southeastern area is small and therefore stochasticity may account for much of this pattern.…”
Section: Age Structure Of Stranded and Incidentally-caught Dolphinsmentioning
confidence: 89%
“…An approach using the northeast Atlantic inshore population as a reference for estimating the length of sexual maturity of stranded dolphins in southern Brazil has been undertaken (Fruet et al, 2012). It was estimated that males and females longer than 318cm and 278cm, respectively, are sexually mature.…”
Section: Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Praderi, 1985), because of the minimal overlap between the distribution of dolphin and artisanal coastal (Franco-Trecu et al, 2009;Zappes et al, 2014) and industrial offshore fishing activities (Domingo et al, 2006). However, bycatch occurs in neighbour areas of southern Brazil (Fruet et al, 2012). Considering the high mobility of this species along the Uruguayan coast (Laporta, 2009) and a potential demographic and genetic connection between dolphins from Uruguay and southern Brazil (e.g.…”
Section: Low Abundance Of Bottlenose Dolphins In Uruguaymentioning
confidence: 99%
“…Bastida et al, 2007;Lodi et al, 2016 this volume), but resident coastal populations are particularly found between southern Brazil (Itajaí River, 26°54'S, 48°38'W) and Argentina (San Antonio Bay, 40°50'S, 64°50'W; Lodi et al, 2016 this volume). Along this area, abundance and other life history traits have been estimated for some of the populations inhabiting protected environments as in Patos Lagoon Estuary (Fruet et al, 2012;2015a, b) and Santo Antonio Lagoon, southern Brazil (Daura-Jorge et al, 2013) and San Matias Gulf, Patagonia, Argentina (Vermeulen and Cammareri, 2009). On the other hand, studies are scarce for bottlenose dolphins occuring in open coastal environments along the SWAO.…”
Section: Introductionmentioning
confidence: 99%